Breast cancer subtype and screening sensitivity in the Quebec Mammography Screening Program. (September 2019) - Perron, Linda; Chang, Sue-Ling; Daigle, Jean-Marc; Vandal, Nathalie; Theberge, Isabelle; Diorio, Caroline; Lemieux, Julie; Pelletier, Eric; Brisson, Jacques
Objective: In mammography screening, interval cancers present a problem. The metric 'screening sensitivity' monitors both how well a programme detects cancers and avoids interval cancers. To our knowledge, the effect of breast cancer surrogate molecular subtypes on screening sensitivity has never been evaluated. We aimed to measure the 2-year screening sensitivity according to breast cancer subtypes. Methods: We studied 734 women with an invasive breast cancer diagnosed between 2003 and 2007 after participating in one regional division of Quebec's Mammography Screening Program. They represented 83% of all participating women with an invasive BC diagnosis in that region for that period. Tumours were categorized into 'luminal A-like', 'luminal B-like', 'triple-negative' and 'HER2-positive' subtypes. We used logistic regression and marginal standardization to estimate screening sensitivity, sensitivity ratios (SR) and sensitivity differences. We also assessed the mediating effect of grade. Results: Adjusted 2-year screening sensitivity was 75.4% in luminal A-like, 66.1% in luminal B-like, 52.9% in triple-negative and 45.3% in HER2-positive, translating into sensitivity ratios of 0.88 (95% confidence interval [CI] = 0.78–0.98) for luminal B-like, 0.70 (CI = 0.56–0.88) for triple-negative and 0.60 (CI = 0.39–0.93) for HER2-positive, when compared with luminal A-like. Grade entirely mediated the subtype-sensitivity association for triple negative and mediated it partly for HER2-positive. Screening round (prevalent vs. incident) did not modify results. Conclusion: There was substantial variation in screening sensitivity according to breast cancer subtypes. Aggressive phenotypes showed the lowest sensitivity, an effect that was mediated by grade. Tailoring screening according to women's subtype risk factors might eventually lead to more efficient programs.